282 Effect of circadian misalignment on the sleep of police officers across a series of night shifts. (3rd May 2021) - Kosmadopoulos, Anastasi; Kervezee, Laura; Boudreau, Philippe; Boivin, Diane
Abstract: Introduction: Misalignment of behavior and circadian rhythms due to night work can impair sleep and waking function. While both simulated and field-based studies suggest that circadian adaptation to a nocturnal schedule is slow, the rates of adaptation in real-world shift-work conditions are still largely unknown. The aim of this study was to evaluate the extent of adaptation of 24-h rhythms in 6-sulfatoxymelatonin (aMT6s) and cortisol in police officers across night shifts and to compare their effect on sleep. Methods: A total of 76 police officers (20 women; aged 32.3±5.5 years, mean±SD) from the province of Québec, Canada, participated in a field study comprising their 28- or 35-day work-cycle. Urine samples were collected for ~24-h before and after a series of 3–7 night shifts. Rhythms of urinary aMT6s were considered adapted if midpoints following night shifts occurred during participants' average daytime sleep period. Cortisol was considered adapted if midpoints occurred within 2h of their average daytime sleep offset. Sleep was measured with actigraphy and sleep logs on a cell phone. Data were analyzed with circular and linear mixed-effects models. Results: Analyses were based on a subset of 37 participants with rhythms of both hormones suitable for circadian phase assessment before and after their series of night shifts. After night shifts, the group acrophase of adapted rhythms (aMT6: n=11, cortisol: n=9) occurred significantly later than for non-adapted rhythms (aMT6s: 10.9 h vs. 3.4 h, p<.001; cortisol: 14.9 vs. 9.9 h, p<.001). Participants with adapted aMT6s rhythms obtained cumulatively more sleep per day throughout the series of shifts than those with non-adapted rhythms (average 6.4 h per day vs 5.8 h per day; p=.026). Conclusion: Consistent with prior research, our results from both urinary aMT6s and cortisol midpoints indicate that a large proportion of police officers remained in a state of circadian misalignment following their night shifts. The minority of officers who adapted to night work were able to obtain more sleep across consecutive night shifts. Support (if any): Project funded by the Institut de Recherche Robert-Sauvé en Santé et en Sécurité du Travail (IRSST). A.K. received a postdoctoral fellowship from the Fonds de Recherche en Santé du Québec (FRQS).